Studies of the life history of school sharks (Galeorhinus galeus) : a thesis submitted in partial fulfilment of the requirements for the degree of Doctor of Philosophy (PhD) in Ecology at Massey University, Albany, New Zealand - Burton, Alex J. C. (Massey University, 2025)
The school shark (Galeorhinus galeus) is a globally distributed, migratory species that was recently reclassified, globally, as Critically Endangered due to all but the New Zealand population having collapsed due to overfishing. Effective management and recovery of these populations is currently limited by a lack of accurate biological information, which is increasingly difficult to obtain due to the scarcity of school sharks throughout their range. By studying the last stable school shark population, located in New Zealand, the aim of this thesis is to provide accurate information on the biology of school sharks to better inform their management worldwide. Specifically, this thesis examines allometric relationships, inter-population variation in life-history stage transitions, intra-population variation in juvenile growth rates, extent of the transfer of elements from mother to pups, and the spatio-temporal connectivity of habitats important to life-history. To enable better standardisation of length data when combining datasets, the optimal model for converting between different length measurements of school sharks was first identified. After standardising length and life-history stage data, a novel Bayesian generative classifier model suggested that length at life-history stage transitions varied among several, globally distributed, school shark populations. A study of juvenile school shark growth across several regions in New Zealand (i.e., Kaipara Harbour, Tasman and Golden Bays, and the Canterbury Bight) revealed that somatic (increase in body length with age) and hepatosomatic (increase of energy stores in the liver with age) growth was consistent among regions, but body condition was generally greater in the Canterbury Bight compared to other two regions. Tracking the year-long, three-dimensional movements of large female school sharks tagged in the Kaipara Harbour with satellite tags showed these sharks dispersed to several potentially important reproductive and feeding habitats around New Zealand. Finally, nutrients and essential and non-essential elements maternally provided to developing young were likely sourced from those assimilated from the mother’s diet during vitellogenesis. This thesis has national and international implications for school sharks and other elasmobranch species, as it provides information and techniques crucial to better understanding the biology of species that is needed to inform more effective management and recovery efforts.
Keywords: school sharks, tope, length-length, reproduction, life-history, growth, maternal transfer, movement, habitat use; Galeorhinus galeus; New Zealand; Geographical distribution; Reproduction; Behavior; Size; 310305 Marine and estuarine ecology (incl. marine ichthyology); 310907 Animal physiological ecology